1986
DOI: 10.1111/j.1365-2559.1986.tb02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in the genital tract in transsexual women following androgen therapy

Abstract: Thirty-two young women who desired sexual reassignment were treated with large doses of androgen for a period of 1 year or more, followed by total hysterectomy. Histological examination revealed marked atrophy of cervical epithelium which could mimic dysplasia, and variable degrees of endometrial atrophy. The ovaries showed occasional corpora lutea indicating that even in the face of long term androgen therapy, ovulation may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 8 publications
3
54
0
2
Order By: Relevance
“…In the study, severe atrophied uterine cervix was found and variable degrees of atrophic change of endometrium were observed as well. [38] Such changes have been also observed in our previous histologic study on the extirpated uterus from 16 FTMs. (Fig.1, Fig.2) These changes are comparable with proliferative change of endometrium in PCOS.…”
Section: The Effect Of the Testosterone On Uterus And Ovarysupporting
confidence: 73%
See 2 more Smart Citations
“…In the study, severe atrophied uterine cervix was found and variable degrees of atrophic change of endometrium were observed as well. [38] Such changes have been also observed in our previous histologic study on the extirpated uterus from 16 FTMs. (Fig.1, Fig.2) These changes are comparable with proliferative change of endometrium in PCOS.…”
Section: The Effect Of the Testosterone On Uterus And Ovarysupporting
confidence: 73%
“…Long-term testosterone use causes vaginal and cervical atrophy [3,17], with decreased vaginal secretion and difficult penetration [12].…”
Section: Masculinizing Effect In Female To Male Hormonal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the introduction, long-term testosterone therapy administered intramuscularly (IM) induces vaginal and cervical atrophy that can alter Pap results and make the exam more difficult. 6,9 Vaginal and cervical atrophy in post-menopausal women results in an elevated proportion of inadequate Pap tests and is ameliorated by short-course topical estrogen cream prior to the Pap; efficacy and acceptability of this treatment in FTMs should be investigated. 26 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In addition, long-term intramuscular androgen administration induces vaginal atrophy 5,7 that may make speculum insertion more painful and cause cervical epithelial atrophy that mimics dysplasia. 9 A qualitative study with six transgender men found that "gynecologic exams are often a unique time when extreme emotional conflict between self-perceptions and physical anatomy are heightened because of physical touch," suggesting unique barriers to screening in this population. 10 No data exist regarding the prevalence of cervical cancer or cervical cancer screening among transgender men.…”
Section: Introductionmentioning
confidence: 99%